Assessing ecosystem response to phosphorus and nitrogen limitation in the Pearl River plume using the Regional Ocean Modeling System (ROMS). Issue 12 (24th December 2014) - Gan, Jianping; Lu, Zhongming; Cheung, Anson; Dai, Minhan; Liang, Linlin; Harrison, Paul J.; Zhao, Xiaozheng
Abstract The effect of phosphorus limitation on the Pearl River plume ecosystem, where large gradients in both nitrogen (N) and phosphorus (P) concentrations exist, is investigated in this process‐oriented study by coupling the Regional Ocean Modeling System (ROMS) model with a new nitrogen, phosphorus, phytoplankton, zooplankton, and detritus (NPPZD) ecosystem model. The results of the N‐based only model of Gan et al. (2010) were compared with those of the new NP‐based model for the plume. The inclusion of P‐limitation noticeably reduces the total phytoplankton production in the plume in the P‐limited near and midfield regions of the plume. However, the nitrate in the plume extends farther downstream and forms a broad area of phytoplankton bloom in the N‐limited far field. Moreover, it changes the photosynthetically active radiation and strengthens the subsurface chlorophyll maximum in the near and midfields, but weakens it in the far field. A high N:P ratio of ∼120 in the near field decreases quickly to a low N:P ratio of <13.3 in the far field due to a higher N:P consumption ratio and mixing with ambient waters with a lower N:P ratio. Mortality and coagulation acts as major sinks for phytoplankton production in the near and midfield during the developmental stage of the bloom, but grazing gradually becomes the most important sink for phytoplankton production in the entire plume during the mature stage. It was shown that the magnitudes of the difference between the NP‐based and N‐based cases decrease sequentially for nutrients, phytoplankton, and zooplankton.